Analysis of Causality Between Economic Growth, Energy Consumption and Carbon Dioxide Emissions in 4 ASEAN Countries - Nuryartono, Nunung; Rifai, Muhamad Amin (International Journal of Energy Economics and Policy, 2017)
Economic growth and energy consumption in 4 ASEAN countries increase in every year. Energy consumption in 4 ASEAN countries is dominated by fossil fuels which increases the carbon dioxide emission. This study examines the causality relationship between economic growth, energy consumption and carbon dioxide emissions in 4 ASEAN countries during the period of 1975 -2013. Methods in this study using Granger Causality and Vector Error Correction Model. The result shows that economic growth and energy consumption in Indonesia and Singapore are not interconnected. While in Malaysia and Thailand, there is a direct causal relationship. A one direction relationship between economic growth and carbon dioxide emissions happened in Indonesia and Thailand, while in Malaysia and Singapore did not exist. Causal relationship between energy consumption and carbon dioxide emissions occurs Indonesia, whereas in other countries did’t exist. The respond of every variables on the shock in other variables are different in each country. Keywords: ASEAN, carbon dioxide emissions, economic growth, energy consumption, granger causality, VECM JEL Classifications: O44, P18, Q40